A new Zr-rich intermetallic phase in an Al-14Si-3Cu-4.5Ni casting alloy with trace additions of Zr. (February 2020) - Jo, Min-Su; Cho, Young-Hee; Lee, Jung-Moo; Kim, Su-Hyeon; Kang, Jun-Yun; Jung, Jae-Gil; Kim, Soo-Bae; Jang, Jae-il
Abstract: A trace addition of Zr to a multicomponent Al-14Si-3Cu-4.5Ni casting alloy has often been found to form a coarse plate-like Zr-rich intermetallic compound with a size of a few tens of μm at the beginning of solidification. Evaluation of the phase composition has confirmed that the Zr-rich intermetallic phase consists of multicomponent constituent elements, mainly Al, Si, Ni and Fe, and is present in a form of (Al, Si)3 (Zr, Ni, Fe). The existence of such a complex (Al, Si)3 (Zr, Ni, Fe) phase has not yet been predicted by phase equilibria calculation of the multicomponent Al-14Si-CuNiMg systems. In this paper, transmission electron microscopy studies combined with electron backscattered diffraction pattern analysis reveals the crystallography information of the (Al, Si)3 (Zr, Ni, Fe) phase for the first time and identifies it as a modified Al3 Zr-D023 crystal (tetragonal, I4/mmm(139)) with slightly changed lattice parameters of a = b = 3.275 Å and c = 15.475 Å. The primary (Al, Si)3 (Zr, Ni, Fe) phase is found to nucleate directly onto AlP particles. The mechanical properties of the Zr-rich intermetallics were also investigated using nanoindentation at both room and elevated temperatures and were compared to those of the Si phase. Highlights: A new Zr-rich intermetallics formed in multicomponent Al-Si alloys was identified. The new (Al, Si)3 (Zr, Ni, Fe) has a tetragonal structure with a = 3.275 Å and c = 15.475 Å. The primary (Al, Si)3 (Zr, Ni, Fe) intermetallics nucleates directly onto AlP particles. Hardness of (Al, Si)3 (Zr, Ni, Fe) intermetallics at room temperature is 11.3 ± 0.5 GPa. The (Al, Si)3 (Zr, Ni, Fe) is thermally stable, retaining the hardness, ~10  GPa at 350 °C.